Code-Switching Practices in Formal Communication Among Members of Australia–Indonesia Youth Association (AIYA) South Sulawesi - Wada'a Gaizhani; Mulyani (AL-MUTSLA, 2026)
Language is a fundamental aspect of communication within bilingual communities, including organizations where more than one language is used. In the Australia–Indonesia Youth Association (AIYA) South Sulawesi, members regularly use both Indonesian and English during formal meetings, making code-switching an integral part of their communication practices. This research aims to identify the types of code-switching used by AIYA South Sulawesi members and to examine the reasons underlying its use. This research employed a qualitative descriptive method, with data collected from two formal meetings of AIYA South Sulawesi. The data were analyzed using Poplack’s (1980) and Yassi’s (2001) frameworks to classify the types of code-switching, and Yassi’s (2016) framework to identify the motivations behind its use. The findings revealed three types of code-switching: intra-sentential, inter-sentential, and tag switching, occurring at the clausal, phrasal, and lexical levels. Intra-sentential switching was the most frequently used type, particularly within the same clause. Twelve motivations for code-switching were identified, with the most dominant being difficulty in finding an appropriate equivalent in Indonesian. These findings indicate that code-switching enables members to use both languages flexibly to support effective communication in formal organizational settings.